Newborn screening and gene therapy in SMA: Challenges related to vaccinations - Kotulska, Katarzyna; Jozwiak, Sergiusz; Jedrzejowska, Maria; Gos, Monika; Ogrodnik, Magdalena; Wysocki, Jacek; Czajka, Hanna; Kuchar, Ernest (Frontiers in Neurology, 2022)
Spinal muscular atrophy (SMA) affects one in 7,500-10,000 newborns. Before the era of disease-modifying therapies, it used to be the major genetic cause of mortality in infants. Currently there are three therapies approved for SMA, including two molecules modifying splicing of SMN2 gene and one gene therapy providing a healthy copy of SMN gene with viral vector. The best effects of any of these therapies are achieved when the treatment is administered in presymptomatic stage of the disease, therefore newborn screening programs are being introduced in many countries. Patients identified in newborns screening might be eligible for gene therapy. However gene therapy and associated administration of steroids in newborns might interfere with vaccinations schedule, which includes live immunization against tuberculosis in some countries. The timing of gene therapy in patients who received live vaccinations has not yet been addressed neither in the clinical trials, nor in the existing international guidelines. The Polish Vaccinology Association has developed first recommendations for gene therapy administration in newborns who received live vaccination against tuberculosis. Their statement was implemented in the current guidelines for Polish SMA patients identified in the newborn screening program and might be helpful for medical professionals in other countries where live vaccine against tuberculosis is still in routine use in newborns.